New species and new synonyms in European Platypalpus (Diptera: Hybotidae) - Barták, Miroslav; Kubík, Štěpán (Zootaxa, 2016)
Platypalpus mosticensis sp. nov. (Czech Republic) and P. ibericus sp. nov. (Portugal) are described and illustrated. The male of Platypalpus silvahumidus Barták & Kubík, 2015 is described and illustrated for the first time. Types of all species of Platypalpus described by Italian entomologist Gianni Raffone between 2002 and 2010 were studied. The following nine new synonyms are proposed: Platypalpus canzonerii Raffone, 2002 = P. maculimanus (Zetterstedt, 1842); Platypalpus litoreus Raffone, 2010 = P. flavicornis (Meigen, 1822); Platypalpus pseudoalter Raffone, 2003 = P. boreoalpinus Frey, 1943; Platypalpus pseudostroblii Raffone, 2002 = P. exilis (Meigen, 1822); Platypalpus subwagneri Raffone, 2003 = P. exilis (Meigen, 1822); Platypalpus romaniolus Raffone, 2010 = P. longiseta (Zetterstedt, 1842); Platypalpus subarticulatus Raffone, 2002 = P. articulatus Macquart, 1827; Platypalpus submaculus Raffone, 2002 = P. macula (Zetterstedt, 1842); Platypalpus subpectoralis Raffone, 2002 = P. pectoralis (Fallén, 1815). Variability in the male genitalia of P. boreoalpinus is discussed.